2016
DOI: 10.1007/s11250-016-1166-7
|View full text |Cite
|
Sign up to set email alerts
|

Short-term dietary concentrate supplementation during estrus synchronization treatment in beef cows increased IGF-I serum concentration but did not affect the reproductive response

Abstract: The objective of this study was to evaluate if short-term dietary concentrate supplementation increased IGF-I serum concentration and resulted in a reproductive response during estrus synchronization treatment in non-lactating beef cows. Thirty non-lactating beef cows (Bos indicus × Bos taurus) were allocated to the same pastureland and fed native tropical grasses as a basal diet. Cows were synchronized using a 7-day CO-Synch plus controlled internal drug release (CIDR) protocol and received fixed time artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
2
0
3
Order By: Relevance
“…To date, a large number of studies have reported the effect of dietary protein concentrate on estrous behavior and reproductive performance of dairy cattle (Law et al, 2009) and beef cattle (Rosales-Torres et al, 2016;Sonjaya et al, 2020). However, there are high variabilities of duration, signs, and intensity of the displayed estrous among individuals and breeds (Moran et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To date, a large number of studies have reported the effect of dietary protein concentrate on estrous behavior and reproductive performance of dairy cattle (Law et al, 2009) and beef cattle (Rosales-Torres et al, 2016;Sonjaya et al, 2020). However, there are high variabilities of duration, signs, and intensity of the displayed estrous among individuals and breeds (Moran et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Si el ovocito ovulado no es fecundado, alrededor de los días 16 y 17 del ciclo estral, el endometrio secretará PGF2α para inducir la regresión del CL (Rosales-Torres & Guzmán, 2011;Sartori & Barros, 2011). Para esto, la PGF2α al unirse a su receptor en los vasos sanguíneos del CL causa una elevación de Ca++ intracelular para inducir vasoconstricción.…”
Section: Control Endocrino Del Ciclo Estral En Bovinosunclassified
“…En vacas lactando tratadas con el protocolo basado en GnRH con y sin el uso de DIP por 7 días, el tiempo entre la aplicación de PGF2-α y la IA, así como los resultados de la TPES reportados fueron muy variables (figura 4C y 4D). En vacas lactando en las que se usó del DIP por 7 días, la TPES más alta (71%) se reportó cuando la IATF se realizó a las 48 (Lamb et al, 2001) y 72 horas (Nash et al, 2012), mientras que la más baja (38%) fue cuando la IA se hizo a las 72 horas (Rosales-Torres et al, 2017). Busch et al (2008), muestran que la TPES es mayor cuando la IA se hace a las 66 horas que cuando se realiza a las 54 horas después del ABANICO VETERINARIO E-ISSN 2448-6132 abanicoveterinario@gmail.com https://abanicoacademico.mx/revistasabanico-version-nueva/index.php/abanico-veterinario Creative Commons (CC BY-NC 4.0) retiro del DIP.…”
Section: Tpes En Vacas Lactando Tratadas Con Protocolos Basados En Gnrhunclassified
See 1 more Smart Citation
“…Research focused on improving the reproductive efficiency in beef females has been ongoing for many years (Diskin and Kenny, 2014). Certain tools such as artificial insemination, embryo transfer, and in vitro fertilization, can be used by producers in the beef industry to improve reproductive efficiency and genetic selection intensity (Rosales-Torres et al, 2017). Despite the advantages these reproductive management tools have to offer, their adoption, particularly in the US, has been slow due to producers concerns related to increased expenses, labor, and risk (USDA, 2017).…”
Section: Introductionmentioning
confidence: 99%